Carbon cycling and burial in New Zealand's fjords - Jessica L. Hinojosa; Christopher M. Moy; Claudine H. Stirling; Gary S. Wilson; Timothy I. Eglinton (Geochemistry, Geophysics, Geosystems)
Abstract Understanding carbon cycling in continental margin settings is critical for constraining the global carbon cycle. Here we apply a multiproxy geochemical approach to evaluate regional carbon cycle dynamics in six New Zealand fjords. Using carbon and nitrogen concentrations and isotopes, lipid biomarkers, and redox‐sensitive element concentrations, we show that the New Zealand fjords have carbon‐rich surface sediments in basins that promote long‐term storage (i.e., semirestricted basins with sediment accumulation rates of up to 4 mm yr−1). Using δ13C distributions to develop a mixing model, we find that organic carbon in fjord sediments is well‐mixed from marine and terrestrial sources in down‐fjord gradients. This is driven by high regional precipitation rates of >6 m yr−1, which promote carbon accumulation in fjord basins through terrestrial runoff. In addition, we have identified at least two euxinic subbasins, based on uranium, molybdenum, iron, and cadmium enrichment, that contain >7% organic carbon. Because the strength and position of the Southern Hemisphere westerly winds control precipitation and fjord circulation, carbon delivery and storage in the region are intimately linked to westerly wind variability. We estimate that the fjord region (759 km2) may be exporting up to 1.4 × 107 kgC yr−1, outpacing other types of continental margins in rates of carbon burial by up to 3 orders of magnitude.